PENGEMBANGAN MODUL DENGAN PENDEKATAN PEMECAHAN MASALAH PADA MATA KULIAH EVALUASI PEMBELAJARAN MATEMATIKA - Nissa, Ita Chairun; Pujilestari, Pujilestari (IKIP Mataram, 2016)
Teachers are professional educators with the primary task of educating, teaching, guiding, directing. train, assess, and evaluate students. Conducting an assessment and evaluation of learners have strategic value because the result can be a material reflection for designing learning mathematics teacher quality. Identify the problem through a questionnaire distributed to students who have carried out Practice Field Experience shows that they still have weaknesses when assessing the understanding of mathematical concepts, procedural knowledge, and problem solving skills. The main obstacle is not available adequate teaching materials for studying these three aspects, necessitating an effort to develop a module for evaluation of learning mathematics courses. The module was developed with the problem solving approach through three stages of adaptation of the model development by Thiagarajan 4D, which define, design and develop. The results of the validation by the two experts of module design are extremely valid with a score of 82.963%, and 91, 852%, and the results of the validation by the two experts of creative content is also very valid with a score of 87.143% and 95.714%. In addition, the result that the use of the modules have an impact on student learning outcomes at tcount = 17.09765>ttable = 2.02439, df = 36, and = 5%. So we concluded that the evaluation of learning course modules that have been developed have valid, practical, and effectivecriteria.